A Woman with Multiple Identities: Reading the Ruth Character in Post-Apartheid South Africa - Masenya, Madipoane (Old Testament essays, 2023)
The word "life" appears in a variety of contexts in Old Testament (OT) scholarship. Included are the use of non-technical senses from ordinary language and the associated folk-philosophical assumptions implicit therein. This article investigates whether and to what extent the recent history of interpretation reflects what the philosopher of religion Don Cupitt refers to as the "turn to life" in everyday speech. To test the hypothesis, samples of the relevant data are selected from the related second-order discourses of popular Bible translations and prominent theologies of the OT. The analysis shows strong correlations in terms of quantitative and qualitative conceptual-historical diachronic variability. Thus, it is concluded that the emergent quasi-religious sense of "life" in ordinary language is also a supervening folk-philosophical concept, concern and category in contemporary OT scholarship. https://doi.org/10.17159/2312-3621/2023/v36n1a11